ANALSIS FAKTOR YANG BERPENGARUH DALAM MEMPREDIKSI LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Djoko Kristianto, Anton Susanto, Fadjar Harimurti & (Universitas Slamet Riyadi, 2016)
This research aims to analyse the effect of changes in profit, changes in receivable, changes in inventories, changes in administrative costs and sales, and changes in gross profit margin in predicting earnings companies listed on the Indonesia Stock Exchange in 2011-2014. Sample taken using purposive sampling method, with a sample of 46 of the 141 companies listed on the Indonesia Stock Exchange in 2011-2014 period. Methods of data analysis using multiple regression analysis. The results of research shows that the changesin profit has positive and signifikan influence on changes in future earnings, changes in receivable, changes in inventories, changes in administrative costs and sales, and changes in gross profit margin hasnot effect on changes in future earningsKeywords: financial statements, financial information, predicting earnings